2017
DOI: 10.3329/jbcps.v35i1.32567
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Sick Neonate: Incidence and Outcome

Abstract: Introduction: Acute kidney injury (AKI) is an important clinical problem in sick neonate. In most patients, AKI accompanies with a predisposing factor such as sepsis, asphyxia and surgery. The aims of this study were to determine the incidence, associated contributing factors and short term outcome of AKI in hospitalized newborn infants. Materials and Methods: This prospective cohort study was done in Dhaka Shishu Hospital from March 2011 to September 2011. This study included 300 sick neonates admitted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…8±202.4 µmol/l), Naveed (265.7±155.7 µmol/l) and Halder (246.4±110 µmol/l). 15,17,19,20,22 The average duration of hospitalization found in the study is lower than those found by Momtaz in 2011 (12.6±1.0 days), by Zulik in 2015 (10.2±3.2 days), and by Ghobrial in 2015 (24.6±13.3 days). 16,23,30 18 Nevertheless, it remains higher than the majority of mortality rates found in other studies.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…8±202.4 µmol/l), Naveed (265.7±155.7 µmol/l) and Halder (246.4±110 µmol/l). 15,17,19,20,22 The average duration of hospitalization found in the study is lower than those found by Momtaz in 2011 (12.6±1.0 days), by Zulik in 2015 (10.2±3.2 days), and by Ghobrial in 2015 (24.6±13.3 days). 16,23,30 18 Nevertheless, it remains higher than the majority of mortality rates found in other studies.…”
Section: Discussionmentioning
confidence: 55%
“…The hospital prevalence of acute renal failure in newborns is poorly known because the majority of published studies are monocentric with variable sample sizes. [15][16][17][18][19][20][21][22] Data found in Middle Eastern countries like India and Pakistan indicate a prevalence that varies between 1.54% and 10.8%. In France, it is estimated between 3 and 10%, which is two times lower than that found in the Anglo-Saxon literature (United States) which is 8 to 24%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, birth asphyxia was responsible for AKI in 14.6% neonates. It was 52.8% in a study by Halder S, et al 24 19 demonstrated that intrinsic AKI, need of mechanical ventilation and dialysis were associated with higher mortality. In our study, the presence of oliguria/acidosis/hyponatremia, high mean serum creatinine level, presence of sepsis/shock, neonates with birth asphyxia/ respiratory distress syndrome, use of mechanical ventilation and requirement of renal replacement therapy were associated with significantly higher mortality.…”
Section: Resultsmentioning
confidence: 95%
“…A multinational, multicentre, observation cohort study7 found that neonates with AKI had a higher mortality compared to those without AKI. Similarly, a higher mortality (21%) was observed by Halder S, et al24 in infants with AKI compared to 10% in infants without AKI.Bolat F, et al15 reported that the use of mechanical ventilation, requirement of peritoneal dialysis, presence of anuria, very low birth weight, bronchopulmonary dysplasia, use of inotropic support, high mean creatinine, high blood urea and low sodium level were the risk factors of mortality in neonates with AKI. In a study by Momtaz HE et al4 , higher mortality was noted in term neonates, female gender, birth weight >2500g, oliguric status and neonates who required dialysis while Pradha DD, et al…”
mentioning
confidence: 81%